CFOA based a new grounded inductor simulator and its applications. (August 2019) - Dogan, Mehmet; Yuce, Erkan
Abstract: A new grounded inductor simulator (GIS) with the property of improved low frequency performance is proposed in this paper. The proposed GIS includes two current feedback operational amplifiers, three resistors and a grounded capacitor. As applications for the proposed GIS, a second-order very high- Q band-pass filter (BPF) and a quadrature oscillator (QO) are given. The very high- Q BPF and the QO have low total harmonic distortion values. Nevertheless, for proper operation, the proposed GIS, the very high- Q BPF and the QO need a single resistive matching constraint. Many SPICE simulations and an experiment for the very high- Q BPF are achieved.